The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1177/23259671211035734
|View full text |Cite
|
Sign up to set email alerts
|

Professional Pitchers Display Differences in UCL Morphology and Elbow Gapping During Moving Valgus Stress Testing After UCL Reconstruction

Abstract: Background: Ulnar collateral ligament (UCL) reconstruction (UCLR) of the elbow has received much attention given the rise in incidence among baseball pitchers. Stress ultrasonography has been demonstrated to be a critical evaluation tool of the UCL. No study has dynamically evaluated the ability of UCLR to restore normal kinematics. Purpose/Hypothesis: The purpose of this study was to compare ulnohumeral gapping during a moving valgus stress test as well as UCL thickness between professional pitchers with and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…The data from Kissenberth et al 2 support increased thickness of the ulnar collateral ligament (UCL) in nondominant (ND) versus dominant (D) elbows. This is counterintuitive and does not coincide with their statement, “The average UCL thickness in UCLR was significantly greater in D elbows compared with ND elbows (1.1 ± 0.09 vs 1.65 ± 0.11 mm; P < .03).” 2(p3) Based on the data presented in parentheses as well as in Figure 3 of their article, this should instead read “thickness in UCLR was significantly less in D elbows….”…”
Section: Inconsistencies In the Reporting Of Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The data from Kissenberth et al 2 support increased thickness of the ulnar collateral ligament (UCL) in nondominant (ND) versus dominant (D) elbows. This is counterintuitive and does not coincide with their statement, “The average UCL thickness in UCLR was significantly greater in D elbows compared with ND elbows (1.1 ± 0.09 vs 1.65 ± 0.11 mm; P < .03).” 2(p3) Based on the data presented in parentheses as well as in Figure 3 of their article, this should instead read “thickness in UCLR was significantly less in D elbows….”…”
Section: Inconsistencies In the Reporting Of Resultsmentioning
confidence: 99%
“…Another source of inconsistency is found in the following statement: “Our study also showed that greater pitching elbow UCL thickness (3.4 mm [D arm] vs 2.8 mm [ND arm]; P < .001) was consistent with previous studies.” 2(p4) These measurements of 3.4 and 2.8 mm are impossible based on the data reported throughout the results. Kissenberth et al 2 reported that the D UCL thickness of the UCL reconstruction (UCLR) and uninjured pitchers averaged 1.1 and 0.17 mm, respectively, while the ND UCL thickness averaged 1.65 and ∼0.17 mm, respectively. While the values mentioned in the discussion section (3.4 mm [D arm] vs 2.8 mm [ND arm]) do align with previously reported values in baseball players, these data points do not appear accurate relative to the values presented throughout the Results section.…”
Section: Inconsistencies In the Reporting Of Resultsmentioning
confidence: 99%
See 3 more Smart Citations